Improvement of nutrient absorption may enhance systemic oxidative stress in cystic fibrosis patients - Galina V. Shmarina; Alexander L. Pukhalsky; Svetlana N. Kokarovtseva; Daria A. Pukhalskaya; Elena A. Kalashnikova; Nikolaï I. Kapranov; Natalia J. Kashirskaja (Hindawi Limited, 2001)
Background: The life expectancy of patients with cystic fibrosis (CF) is largely dependent on the pulmonary disease severity and progress. Malnutrition may be an important complicating factor in active and chronic lung disease.